ROBOT DETEKSI GARIS MENGGUNAKAN SENSOR INFRA MERAH (INTERFACE USB) - Nanan Rohman; Dadang Nurdiansyah (STMIK Mardira Indonesia, Bandung, 2015)
In designing Robot Follow Line based on Microcontroller MA 8535, I faced same problems, such as how its hardware is designed and how this program design functions to run the system of the series. The aim of designing this system is in order to aware human to know the functions of the robot in simplifying human word. Basically, this system series is designed to change the signal analog on a censor to became a digital value and finally become move. Having tested the system resulting that the system with C language is capable to give the instructive signal to the hardware to such instructions the form of a move. It is to conclude that the tool functions well and the output is suitable to the expectation and conforms to the initial aim of the research and the designing of this robot. Key Word: Robot Line Follow, Microcontroller ATMEGA MA 8535 v.2.0, Infrared, Foto Dioda, Comparator.